사탕수수와 커피로 얽힌 이민자의 메커니즘: 브라질 이민자 사례를 중심으로 - 손지혜(Son, Jihye) (Asian journal of Latin American studies, 2024)
This study examines the history of immigration to Brazil with a focus on the sugarcane and coffee industries, exploring the economic activities and transnational network formation processes of major immigrant groups, including African slaves, European immigrants, and Asian immigrants. By applying the theoretical frameworks of diaspora and transnationalism, the study compares and analyzes how these groups maintained connections with their countries of origin while adapting and contributing to Brazilian society. Particularly, the study investigates the role changes among immigrant groups within the economic contexts of the sugarcane cycle (16th–18th century) and the coffee cycle (19th–early 20th century). During the sugarcane cycle, Brazil's economic structure heavily relied on African slave labor, characterized by forced migration. In contrast, the coffee cycle witnessed the centrality of European and Asian immigrants' economic activities and the formation of transnational networks. The research evaluates the nature of the economic and social networks established by each group postmigration, highlighting the importance of comparative analyses of immigrant groups, which have been underexplored in previous studies. This paper presents the following key insights. First, it utilizes the concepts of diaspora and transnationalism to provide a more nuanced understanding of the historical experiences of Brazilian immigrants. Second, it demonstrates the economic roles and cultural contributions of transnational networks through data and case studies. Third, by analyzing the economic and cultural impacts of Asian immigrants, particularly Japanese and Chinese communities, the study adds originality to the existing literature, which has often overlooked these groups. This research reveals that Brazil’s immigration history is not limited to economic contributions but also encompasses the significant roles that immigrant groups played in the processes of social and cultural integration through their historical experiences and networks. It provides critical insights into modern migration studies and a deeper understanding of Brazil's multicultural identity. KCI Citation Count: 0